Analysis of Demersal Fish Schooling Distribution in Tarakan Waters North Borneo by Using Hidroacoustic Method - Susilawati '; Aras Mulyadi; Mubarak ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research is aimed to determine the distribution of demersal fish schooling and the relation between demersal fish schooling and temperature, salinity and depth of water by using hydroacoustic method. The research was held in August 2014 at the Research Institute of Marine Fisheries Laboratory of Muara Baru, North Jakarta. This research used hydroacoustic method with acoustic descriptor techniques. The amount of fish schooling was obtained by digitization and integration, the values of integration would have generated the position and depth of the waters. Demersal fish schooling which found in waters of Tarakan were comprising of 19 schooling. The dominant fish schooling occured at temperature of 270 C to 280 C and tended to be appear at salinity of 35.5 ‰. Type of demersal fish schooling in Tarakan waters was mostly emerged in form of horizontal contained in the bottom of ocean.Keywords :Kalimantan, Tarakan, Demersal Fish, Fish Schooling , Hydroacoustic